Fibrinolytic Therapy in Thrombosis of Mechanical Valves: Outcomes and Complications - Ali Nasri Nasrabadi; Fahime Yarhamadi; Afshin Amirpour; Reihane Zavar; Mojtaba Akbari (ARYA Atherosclerosis, 2023)
INTRODUCTION: Valvular heart disease presents a significant and escalating global health challenge. Prosthetic valve thrombosis (PVT) following surgical valve replacement is a primary cause of valve failure. The aim of this study was to ascertain the outcomes and complications of fibrinolytic therapy in patients diagnosed with PVT.METHOD: This cross-sectional study enrolled 81 patients diagnosed with PVT who underwent fibrinolytic therapy between 2008 and 2018. Streptokinase was administered to 87.6% of patients, while 12.4% received reteplase. All demographic and clinical data were gathered from the patients’ medical records. The incidence of successful recovery and complications were assessed.RESULTS: The records of 81 patients (43.2% male, mean age: 51.6 ± 13.9 years) were examined. The findings revealed that 59% and 35% of the patients had mitral and aortic PVT, respectively. While 12% of the patients experienced drug complications, 90% achieved successful recovery. Stroke and severe hemorrhage were complications frequently reported by the patients treated with streptokinase (8% and 4% respectively). The patients treated with reteplase demonstrated a 100% recovery rate. Conversely, 89% of the patients treated with streptokinase achieved successful recovery, and 7% of the patients experienced a partial recovery.CONCLUSION: Fibrinolytic agents can serve as an effective treatment with an excellent success rate for managing PVT in patients post-surgical valve replacement.